2020
DOI: 10.1080/00131881.2020.1794924
|View full text |Cite
|
Sign up to set email alerts
|

Significant events and the role of emotion along doctoral researcher personal trajectories

Abstract: Background: This study focuses on furthering the understanding of doctoral researcher development, through the examination of significant events and application of the trajectories analysis framework. Conducting doctoral studies requires a high level of cognitive, personal and emotional competency. Students experience positive and negative emotions that affect their confidence and their performance, in both their doctoral studies and their personal life. Purpose: The aim of the study was to analyse, in depth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Previous reports of the elation of completing one's doctoral research (Peterson, 2011;Weise et al, 2020) similarly resonated with the ECRS in our study, as Cameron's comment illustrates:…”
Section: A Continuum Of Liminality Experience Identity Construction A...supporting
confidence: 77%
“…Previous reports of the elation of completing one's doctoral research (Peterson, 2011;Weise et al, 2020) similarly resonated with the ECRS in our study, as Cameron's comment illustrates:…”
Section: A Continuum Of Liminality Experience Identity Construction A...supporting
confidence: 77%
“…These aspects included doctoral students' motivation and the characteristics of goal-directedness and the concept of self (Bair & Haworth, 2004); intelligence, knowledge, thinking style (Lovitts, 2005); and also, competencies (Cornér et al, 2019;Leijen et al, 2016). Weise et al (2020) found that reassessment of the competencies in the research process due to the pressure to publish was one of the frequent challenges that doctoral students experienced, and that responding to this challenge required "a high tolerance for frustration and the ability to manage negative feelings such as insecurity, rejection, and failure" (p. 15). Also, health and family influenced doctoral students' personal resourcefulness and thus their studies (Katz, 2018;McAlpine et al, 2012) and wellbeing (Cornér et al, 2017;Pyhältö et al, 2012a).…”
Section: Challenges On Individual and Structural Level Of Doctoral Edmentioning
confidence: 99%
“…According to Lee (2008), supervision had the most powerful impact on the doctoral study process. Several authors have previously reported how the quality of supervision influenced the duration of studies, the well-being of doctoral students (Peltonen et al, 2017;Pyhältö et al, 2012a;Weise et al, 2020), their satisfaction with studies, and the development of their competencies (Peltonen et al, 2017;Pyhältö et al, 2012a). Change of supervisors, unmet expectations for communication and guidance, as well as conflicts between supervisors, led to supervisor-related stress (Cornwall et al, 2019).…”
Section: Challenges On Individual and Structural Level Of Doctoral Edmentioning
confidence: 99%
See 1 more Smart Citation